Marketing strategy and communication of Red Bull Česká republika, s.r.o. - Reindl, Martin (2018)
Red Bull is considered to be an international corporate. In my bachelor thesis I will try to appropriately describe activities along with other aspects connected this company. Also, I will pay attention to brand awareness and brand image of Red Bull.In the first part of my thesis I will define all necessary aspects to understand given problematic from the theoretical point of view. In the second part, I will mention several actions of a given company as well as implement knowledge from the first part. Towards the end, I have prepared a survey with answers, which will be supported by the previously collected information and data. In this thesis will be revealed the true awareness and image of the brand along with the current marketing strategy of Red Bull. Recommendations to Red Bull for its further run of the business will be provided along.